Behind The Tradition of Draining Sendhang Kakung Lan Putri in Klaruan Village, Mojolaban, Sukoharjo - Sawitri Sawitri (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
ABSTRACT The tradition of Nguras Sendhang (or draining Sendhang) is an hereditary heritage still held until today. Tradition of Nguras Sendhang exists in Klaruan Hamlet, Palur Village, Mojolaban Sub District, Sukoharjo Regency. The tradition is held annually in Besar month of Javanese year using a variety of sesaji (meal offrering), including: nasi tumpeng gurih, golong asahan, jajan pasar, srundeng, sambel goreng, kerupuk, ingkung, peyek, jerohan (rempelo ati, usus, babat, kebuk, limpa), gudangan, pisang satu tangkep, bunga tujuh warna, takir tujuh. All sesajis were put on the building/pendhopo close to the sendhang. Kondangan rite was attended by all members of society and prayed for by modin or village elders. Sesajis were provided collectively by the members of society and having been prayed for (dikundangi/diujubke) some of sesajis were eaten together and the rest were brought home. The uniqueness of nguras sendhang tradition is that after the kondhangan procession, the people may not bring their own sesaji home but they should bring others’ home. In the nguras sendhang tradition, there was also wayang performance held at night, the cost of which was paid collectively by the members of society. The performance is held along day and night with different narrators (dalangs) but same story. The uniqueness also lies in the narrators who were not allowed to take wage for their job. There is a myth that if this rite is not held, some disasters will occur, one of which is fire. House fire incidence occurring frequently makes life uneasy.Keywords: Ceremony, tradition, nguras sendhang, rite, myth